Diversity in the Family of Manganese Oxides at the Nanoscale: From Fundamentals to Applications - Ghosh, Sujit Kumar (ACS omega, 2020)
The interesting chemistry of manganese is due to its various oxidation states. The possibility of several oxidation states has offered the element a special position among the transition metal elements in the periodic table. Amidst the possible oxidation states of manganese (in the range of −3 to +7), the +2, +3, and +4 oxidation states are the most prevalent in nature. Manganese possesses the ability to form multiple bonds with oxygen through spontaneous oxidation to a variety of stoichiometric oxides/hydroxides/oxyhydroxides that are collectively coined as “manganese oxides”. However, using the recent advances in the synthetic strategies and characterization techniques over the past couple of decades, the investigation of the physicochemical properties of manganese oxides has been extended up to the nanoscale dimensions beyond the molecular. Moreover, the family of the manganese oxides also includes a series of porous architectures that are, often, stabilized at the nanoscale dimensions. Exquisite synthetic control over the size, shape, organization, and mass production of a variety of oxides at the nanoscale dimensions renders outstanding structural, optical, catalytic, magnetic, and transport properties. The tunable properties along with the chemical and biological accessibility open up new opportunities in a diverse range of niche applications critical to global society. Therefore, beyond the multivariance, polymorphism, thermodynamics, phase transition, crystallinity, magnetism, semiconducting behavior, and biogenecity may serve as the key factors to describe the compelling applications in health and other fields and to further understand the manganese oxides at the nanoscale.